Pengaruh Rezim Ekonomi Politik Terhadap Economic Security Pasca People’s War di Nepal - Hidayat Chusnul Chotimah (Jurnal Ilmiah Hubungan Internasional, 2020)
AbstractThe ten years People’s war or civil war in Nepal during 1996-2006, has resulted in human insecurity particularly the threat of economic security and personal security. The existence of political and economic regime brought after the end of civil war in Nepal has led to structural violence for communities such as the deprivation of political, economic and social rights. This paper will explain how the influence of political and economic regime syndicate brought after Nepal's civil war to human security, particularly on economic security dimensions and efforts to overcome it. The study uses descriptive qualitative analysis through literature study that collected from journal articles and previous research reports. The results show that the existence pf political and economic regime in Nepal has brought Nepal as one of the world's poorest countries in the dimensions of monetary and non-monetary poverty. For that reason, social protection and foreign assistance are required to build a positive peace in Nepal.  Abstrak Perang sipil atau yang disebut sebagai Peole’s War selama sepuluh tahun di Nepal antara tahun 19998-2006 telah mengakibatkan human insecurity khususnya terkait ancaman keamanan ekonomi dan keamanan individu (person) bagi masyarakat di Nepal. Keberadaan rezim ekonomi politik yang dibawa pasca berakhirnya perang sipil di Nepal telah menimbulkan adanya kekerasan struktural yang dialami oleh masyarakat seperti perampasan hak politik, ekonomi maupun sosial. Tulisan ini akan menjelaskan bagaimana pengaruh sindikat rezim politik dan ekonomi yang dibawa setelah perang sipil di Nepal terhadap keamanan manusia (human security) khususnya pada aspek keamanan ekonomi dan upaya untuk mengatasi hal tersebut. Kajian dalam tulisan ini menggunakan analisis deskriptif kualitatif melalui studi pustaka yang dikumpukan dari artikel jurnal maupun laporan penelitian terdahulu. Hasil kajian menunjukkan bahwa keberadaan rezim politik dan ekonomi di Nepal telah membawa Nepal sebagai salah satu negara termiskin di dunia dalam dimensi kemiskinan moneter dan non-moneter. Untuk itu, upaya perlindungan sosial dan bantuan asing sangat diperlukan dalam rangka mewujudkan perdamaian positif di Nepal.